Two new genera of hard ticks, Robertsicus n. gen. and Archaeocroton n. gen., and the solution to the mystery of Hoogstraal’s and Kaufman’s “primitive” tick from the Carpathian Mountains - Barker, Stephen C.; Burger, Thomas D. (Zootaxa, 2018)
We establish two new monotypic genera, Robertsicus n. gen. and Archaeocroton n. gen., based on two enigmatic species of Amblyomma. Robertsicus, with the type species R. elaphensis (Price, 1959) n. comb., is proposed for Amblyomma elaphense, the tick of the Trans-Pecos rat-snake of the Chihuahuan Desert of Mexico and southeastern USA (parts of Arizona, West Texas and New Mexico). Archaeocroton, with the type species Ar. sphenodonti (Dumbleton, 1943) n. comb., is proposed for Amblyomma sphenodonti, the tuatara tick of New Zealand. This is another step in the resolution of the systematic problems concerning the genus Aponomma, a heterogeneous group of eyeless ticks with a predilection for reptiles. By removing R. elaphensis (Price, 1959) and Ar. sphenodonti (Dumbleton, 1943) from the genus Amblyomma we have resolved, for now at least, the polyphyly of the genus Amblyomma. We have also resolved a 50-year old mystery: the identity of Hoogstraal’s and Kaufman’s “primitive” tick from the Carpathian Mountains that had a “striking resemblance” to Ar. sphenodonti n. comb.; it was an Ar. sphenodonti n. comb. that had travelled to the Carpathian Mountains from New Zealand on a captive tuatara.